2016
DOI: 10.1248/bpb.b16-00255
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Staphylococcal Toxins and Clinical Outcomes of Methicillin-Resistant <i>Staphylococcus aureus</i> Bacteremia

Abstract: It is well known that methicillin-resistantVancomycin (VCM) has been the standard treatment for MRSA infections for over 50 years. The area under the concentration-time curve [AUC/minimum inhibitory concentration (MIC) ratio] is a representative parameter of the pharmacokinetics-pharmacodynamics (PK-PD) of VCM.3) The Infectious Diseases Society of America recommends a target AUC/ MIC>400 for the treatment of severe MRSA infections. 4)However, this is often difficult to achieve for MRSA strains with high VCM MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Previous studies have reported the association between the virulence factors and mortality rate in patients with MRSAB. Masayuki et al reported the independent association between superantigenic toxins (SAgT) such as TSST‐1 and SEs and 30‐day mortality in MRSAB . Furthermore, Park et al reported that three staphylococcal superantigen genes ( sec , sel , and tst ) causing bloodstream infection were associated with mortality …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported the association between the virulence factors and mortality rate in patients with MRSAB. Masayuki et al reported the independent association between superantigenic toxins (SAgT) such as TSST‐1 and SEs and 30‐day mortality in MRSAB . Furthermore, Park et al reported that three staphylococcal superantigen genes ( sec , sel , and tst ) causing bloodstream infection were associated with mortality …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Methicillin-resistant Staphylococcus aureus is known to produce various virulence factors, including staphylococcal enterotoxins (SEs), toxic shock syndrome toxin-1 (TSST-1), leukocidins, hemolysins, and exfoliative toxins, and immune-modulatory factors. 14 Previous studies have reported the association between the virulence factors and mortality rate in patients with MRSAB. Masayuki et al reported the independent association between superantigenic toxins (SAgT) such as TSST-1 and SEs and 30-day mortality in MRSAB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of these additional factors demonstrated a significant impact on 28-day mortality when calculating a pathogen adapted Cox model. However, other prominent virulence factors like toxic shock syndrome toxin or staphylococcal enterotoxins, which were previously reported as independent risk factors for 30-day mortality, were not determined in the present study (Maeda et al, 2016). By using cluster analysis, which was previously used to study the effect of genetic and biofilm formation capacity characteristics on patients' outcomes, the present study investigated the sole impact of bacterial genetic factors on mortality in a cohort of SAB patients (Cremers et al, 2019;Seymour et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…Considering the major impact of S. aureus on human coagulation, mediated by the vast amount of virulence factors interacting with fibrinogen, the influence of fibrinogen in that study might have been underestimated. Other studies investigating large collectives of patients with SAB did not include fibrinogen in their analysis or studies investigating sepsis in general did show a link between fibrinogen and mortality but did not state any causative pathogen (Fowler et al, 2005;Cagatay et al, 2007;Forstner et al, 2013;Maeda et al, 2016;Holmes et al, 2018;Guilamet et al, 2019;Xia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%